Deskripsi Pemahaman Konsep Mahasiswa pada Materi Hidrokarbon - Tamrin Taher (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to describe students' understanding of concepts in basic chemistry course I for the material of hydrocarbons. This research uses a descriptive quantitative approach. The research subjects were 21 semester I students of the Tadris biology and mathematics study programs who were programming basic chemistry courses I. Data collection techniques used test questions with data analysis using descriptive quantitative. The results showed that 30% of the students answered correctly the name of the alkane compound, 21% answered correctly the name of the alkene, 30% answered correctly the name of the alkyne, 67% answered correctly the concept of the position of the carbon atom, 40% were able to write the structure of the hydrocarbon compound based on the name given. given, 20% of students were able to write isomers of hydrocarbon compounds